2016
DOI: 10.1038/srep33162
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis exploits the formation of new blood vessels for its dissemination

Abstract: The mechanisms by which the airborne pathogen Mycobacterium tuberculosis spreads within the lung and leaves its primary niche to colonize other organs, thus inducing extrapulmonary forms of tuberculosis (TB) in humans, remains poorly understood. Herein, we used a transcriptomic approach to investigate the host cell gene expression profile in M. tuberculosis–infected human macrophages (ΜΦ). We identified 33 genes, encoding proteins involved in angiogenesis, for which the expression was significantly modified du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 59 publications
(84 reference statements)
6
87
2
1
Order By: Relevance
“…Previously, it has been shown that upregulation of vascular endothelial growth factor (VEGF) had a promoting effect on macrophage‐mediated extra pulmonary dissemination of M. tuberculosis (Polena et al, 2016). To examine the role of VEGF in our zebrafish model, we systemically infected Tg(kdrl:mCherry) is5 embryos with M. marinum .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been shown that upregulation of vascular endothelial growth factor (VEGF) had a promoting effect on macrophage‐mediated extra pulmonary dissemination of M. tuberculosis (Polena et al, 2016). To examine the role of VEGF in our zebrafish model, we systemically infected Tg(kdrl:mCherry) is5 embryos with M. marinum .…”
Section: Resultsmentioning
confidence: 99%
“…The observed colocalisation of intensified kdrl/vegfr2 signal with M. marinum ‐ loaded phagocytes in larval brain blood vessels in our study suggests an interaction between infected macrophages and the blood vessel wall and a role for VEGF in this process. It has been shown that macrophages secrete VEGF after infection with M. tuberculosis in an ESX‐1‐dependent manner, which in turn interacts with VEGFR2 specifically (Polena et al, 2016). This mechanism is essential for angiogenetic vessel growth and bacterial expansion and dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of vasculogenesis-focused HDT for TB is likely to depend on the stage of disease and the treatment objective, namely, interference with either angiogenesis or vascular permeability. In patients with active TB, factors that induce neovascularization, notably vascular endothelial growth factor (VEGF) and its receptor VEGFR, are abundant in the circulation [238][239][240] and have been proposed as biomarkers of disease severity 241 . Bevacizumab, a mAb against VEGF, is approved for the treatment of certain cancers, and several other antibodies that target VEGF or VEGFR are in clinical trials.…”
Section: Targeting Vascular Biology In Tb Granulomamentioning
confidence: 99%
“…In animal models of TB, VEGF and VEGFR inhibitors have revealed beneficial effects when given in combination with conventional drugs, by limiting bacterial dissemination and boosting the activity of drugs that target hypoxic Mtb 242,243 . Conversely, there is a risk that the administration of such biologics without concurrent chemotherapy may promote TB reactivation 244,245 and bacillary dissemination 240 .…”
Section: Targeting Vascular Biology In Tb Granulomamentioning
confidence: 99%